Landscape change and its effects on the visual experience of a case study area in the Öresunds region - Åsa Ode (European Regional Science Association (ERSA), 2004)
The study focuses on landscape change, from an historical perspective (year 1915) and as a discussion of future changes (year 2015) for a case study area in southern Sweden. The historical situation is based on map data while the situation of 2015 is a predictive modelling based on spatial planning and policy documents for the case study area. The study identifies changes in land cover and their spatial distribution within the landscape. The result is discussed in relation to perceived change as well as the areas sensitivity to change. The paper further outlines implications of the result for management and planning in the context of the European Landscape Convention.
Keywords: 330